Differences in Motivation and Learning Outcomoes Using The Index Card Match and Index Card Sort Leraning Models in Biology Subjects at SMA Negeri 10 Mukomuko - Niken Safariah; Hartati, Merri Sri; Rizki Pratama (Multidisciplinary Journals, 2025)
This study aims to determine the differences in student motivation and learning outcomes using the index card match (ICM) and index card sort (ICS) learning model in biology subjects at SMA Negeri 10 Mukomuko Regency. The research method used is observation with qualitative approach. The population in this study consisted of 10th-grade science students, with samples taken from two classes applied consecutvely. The study was conducted in pre-existing classes : Class X IPA 1, Class IPA 2, and Class IPA 3, with a total of 75 students. The results of the study indecate that learning using the ICM model in the experimental class led to an increase in motivation, as avidenced by the questionnaire results. Similarly, the ICS model in experimental class also showed increased motivation based on the scores obtained. In terms of learning outcomes, both experimntal classes experinced an improvment in scores. However, there was no significant or statistically distinct difference in leraning outcomes between the two models.